2001
DOI: 10.1238/physica.regular.063a00036
|View full text |Cite
|
Sign up to set email alerts
|

Quadrupole and Octopole Electromagnetic Waves in Slightly Non-Uniform Magnetized Plasma Column

Abstract: The effects of substrate temperature on optoelectronic and structural properties of undoped microcrystalline silicon thin films have been investigated. The undoped silicon films have been deposited by the very high frequency plasma enhanced chemical vapor deposition (VHF-PECVD) technique using a SiH 4 and H 2 gas mixture at 105 MHz plasma excitation frequency and moderately low power density of 70 mW/cm 2 . The effect of the systematic variation of substrate temperature (from 180 C to 370 C) on film properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…If this peculiarity is not taken into account, it is possible to obtain nonphysical solutions in the region of the point where k 1 = k 2 . The research carried out has shown that this special point is a point of wave type changing [12].…”
Section: Rmentioning
confidence: 89%
See 4 more Smart Citations
“…If this peculiarity is not taken into account, it is possible to obtain nonphysical solutions in the region of the point where k 1 = k 2 . The research carried out has shown that this special point is a point of wave type changing [12].…”
Section: Rmentioning
confidence: 89%
“…For arbitrary values of plasma column radius and external magnetic field value the local dispersion equation (9) can be solved only with the help of numerical methods. The detailed analysis of the local dispersion equation for the wave in m = ±2 and in m = ±3 modes was studied in our previous paper [12]. Here we represent some new data which is necessary for plasma density axial profile study.…”
Section: Local Dispersion Equationmentioning
confidence: 93%
See 3 more Smart Citations